Inducirane fazne spremembe v kristalih n-Mo4O11 s pomočjo ultrahitrih laserskih sunkov - Borovšak, Miloš (Anali PAZU, 2020)
The article presents the experimental result of fluence dependence of the transient reflectivity response to ultra-fast laser pulses in n-Mo4O11 crystals. Results of the experiment show that at certain fluences at low temperatures phase changes can be induced in the crystals which are not seen inthe temperature phase diagram.
Keywords: fazne spremembe; kristali; molibdenovi oksidi; molybdenum oxides; phase changes; ultra hitra optična spektroskopija; ultra-fast optical spectroscopy